(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
تُسهم أجهزة الـطبقي المحوري المبرمج( CT ) بأكثر من 34% من الجرع المحسوبة في فحوصات الأشعة السينية في العالم( UNSCEAR, 2000)، وتعد الجرعة الإشعاعية الناتجة عن تصوير الأطفال بأجهزة الـ CT مهمة بشكل خاص، لأن الأطفال أكثر حساسية وعرضة لحدوث السرطانات من البالغين. يدرس هذا البحث الجرعة الإشعاعية للمرضى ( البالغين، الأطفال) الناتجة عن جهاز التصوير الطبقي المبرمج في سورية (30 جهاز لـ 6 شركات صانعة مختلفة). وقد تضمن قياسات الجرعة الإشعاعية قياس كلٍ من قرينة الجرعة للطبقي المبرمج، معامل الجرعة الطولي والجرعة الفعالة. من خلال نتائج الدراسة، وجد أنّ معظم قيم معامل الجرعة الطولي وقرينة الجرعة كانت أخفض من المستويات المرجعية الأوريبة باستثناء بروتوكول تصوير الصدر بدقة عالية، حيث كان معامل الجرعة الطولي أعلى من المستويات المرجعية للهيئة الدولية للوقاية الإشعاعية. As per UNSCEAR 2000, CT contributes over 34% of collective dose from diagnostic X-Ray examinations in the world. The radiation dose in CT has a particular importance for children. It is very well known that children are likely to be more sensitive to get radiation induced cancer than adults. This paper discusses the radiation dose of patients (adults and children) in Computed Tomography in Syria (/30/ CT units for /6/ different manufacturers). The radiation dose measurement has covered computed tomography dose index, dose length product and effective dose. The results show that most computed tomography dose index and dose length product values recorded were below dose reference levels, only for high resolution chest protocol, the dose length product results were higher than the International Commission on Radiological Protection.